Diallel analysis for seed-cotton yield and its contributing traits in upland cotton (Gossypium hirsutum) - AHMAD, RANA TAUQEER; KHAN, IFTIKHAR AHMAD; ZUBAIR, MOHAMMAD (The Indian Journal of Agricultural Sciences, 2013)
Four upland cotton (Gossypium hirsutum L.) varieties were genetically analysed for gene action controlling the phenotypic expression of seed-cotton yield and its related traits. Additive type of gene action with partial dominance was observed for boll number/plant, boll weight, seed-cotton yield and seed index. Epistatic effects were also Involved in the expression of all the characters except boll weight.